One decade of glioblastoma multiforme surgery in 342 elderly patients: what have we learned? - Heiland, Dieter Henrik; Haaker, Gerrit; Watzlawick, Ralf; Delev, Daniel; Masalha, Waseem; Franco, Pamela; Machein, Marcia; Staszewski, Ori; Oelhke, Oliver; Nicolay, Nils Henrik; Schnell, Oliver (Journal of Neuro-Oncology, 2018)
Introduction Glioblastoma multiforme (GBM) is the most common malignant primary brain tumor in adults with peak incidence in patients older than 65 years. These patients are mostly underrepresented in clinical trials and often undertreated due to concomitant diseases. Recently, different therapeutic approaches for elderly patients with GBM were discussed. To date, there is no defined standard treatment. The aim of the present study is to evaluate the functional and oncological outcome in surgical treatment of elderly patients. Materials and methods A total of 342 elderly patients aged ≥ 65 years were retrospectively analyzed in our neurosurgical center. Surgical therapy, adjuvant treatment, overall survival (OS) and functional outcome using Karnofsky performance scale (KPS) and Neurological assessment of neuro-oncology-score were analyzed. Results The median age at GBM diagnosis was 73.4 (IQR 9.28) years. Median overall survival was 7.5 (CI 95% 6.0–9.1) months and median preoperative or postoperative KPS was 80 (IQR 20). Surgical resection was performed in 216 (63.2%) patients, in 125 patients (36.5%) patients a stereotactic biopsy was performed. The median OS was significantly higher in patients with gross total resection (GTR) compared to partial resection and biopsy (10.8 months; CI 95% 9.5–12.3). Patients with combined radio-and chemo-therapy (RCT) showed significant longer OS, particularly MGMT-negative GBM. Higher preoperative KPS was found to be associated with improved overall survival. Conclusion GTR and adjuvant combined RCT provides benefits for overall survival in elderly patients. Therapy decision should be made in regard to preoperative functional status instead of biological age.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Elderly patients; Glioblastoma multiforme; NANO-score; Radiochemotherapy